ANALYSIS OF SHIP BEHAVIOR UNDER INFLUENCE OF WAVES AND CURRENTS - Armudi, A.; Marques, W. C.; Oleinik, P. H. (Revista de Engenharia Térmica, 2017)
The most important environmental factors related to safety of ship and performance on high sea are surface winds and waves. In order to obtain an optimal trajectory of a ship route, it is a prerequisite to know the sea state condition, as well as, the behavior of the ship in waves and currents. The purpose of this study is to analyze the ship behavior under the influence of 3 different sea state conditions over the Southern Brazilian inner shelf near the Rio Grande coastal region. SHIPMOVE and TOMAWAC + TELEMAC3D system were simulated under three different wave scenarios. Day 4 showed the shortest traveled distance and lowest velocity. The sea state of Day 33 deflected the initial vessel path northeasterly and generated high rotational motions. Day 100 depicted the longest final displacement and highest average velocity, where this event showed the most smooth sea state condition. Lastly, the ship behavior seems to be strongly influenced by the sea state condition for the three events.